Integrated transcriptomic and metabolomic analyses reveal optimized cultivation strategies for purple potatoes (Solanum tuberosum L.) - Zhong, Weiran; Yang, Jin; Liang, Fengming; Ma, Qiang (Frontiers in Plant Science, 2025)
Potato (Solanum tuberosum L.), a cornerstone of global food security, faces significant yield limitations worldwide. Fertilization regimes and planting density critically determine potato yield and quality. This study integrated transcriptomic and metabolomic analyses to investigate the effects of basal fertilizer rates and planting density on tuber yield and quality in the purple cultivar ‘Jinyun No. 5’, aiming to establish sustainable high-efficiency cultivation protocols for pigmented potatoes. In the mountainous areas of southern China, the optimal combination (0.15 kg·m-² basal fertilizer and 5.25 plants·m-²) significantly enhanced yield, anthocyanin, and starch content. Yield increased by 12.9% versus minimum density (3.75 plants·m-²) at equivalent fertilization, and by 6.6% versus minimum fertilization (0.05 kg·m-²) at equivalent density. Metabolomic profiling revealed marked accumulation of flavonoids and phenolic acids under optimal conditions, while transcriptome sequencing identified upregulation of key genes involved in anthocyanin biosynthesis (ANS, DFR) and starch metabolism (SBEI, SBEII). These findings provide molecular insights into how optimized cultivation strategies improve both yield and nutritional quality in purple potatoes.